2019
DOI: 10.1039/c8cc08733d
|View full text |Cite
|
Sign up to set email alerts
|

Single-site labeling of histidine in proteins, on-demand reversibility, and traceless metal-free protein purification

Abstract: A precision methodology distinguishes one His from all the nucleophilic residues and its multiple copies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Next, we selected ubiquitin (1 d) with one N a -NH 2 and seven N e -NH 2 groups. The LDM K-K reagents 4 a and 4 c-4 f led to 15,10,8,13, and 5 % conversion, respectively (Figures S47-S51). To our delight, the LDM K-K reagent 4 b proved successful in rendering single-site (K6) labeled ubiquitin 6 d (35 % conv., Figures 3 and S27).…”
Section: Angewandte Chemiementioning
confidence: 98%
See 2 more Smart Citations
“…Next, we selected ubiquitin (1 d) with one N a -NH 2 and seven N e -NH 2 groups. The LDM K-K reagents 4 a and 4 c-4 f led to 15,10,8,13, and 5 % conversion, respectively (Figures S47-S51). To our delight, the LDM K-K reagent 4 b proved successful in rendering single-site (K6) labeled ubiquitin 6 d (35 % conv., Figures 3 and S27).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…After successful demonstration of LDM K-K with proteins bearing moderate number of primary amines, we selected a-lactalbumin, cytochrome C, and myoglobin with higher number of primary amines (13)(14)(15)(16)(17)(18)(19)(20). The vortexing of a-lactalbumin 1 e (one N a -NH 2 and twelve N e -NH 2 ) with 4 a renders mono-labeled product 6 e (37 % conv., Figures 3 and S28).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Peptides are excellent scaffolds for biological studies, as they can be used to monitor highly specific molecular interactions with a broad range of biomolecules. Fluorescent peptides have traditionally been synthesized by coupling fluorophores to reactive groups (initially to amines, carboxylic acids and thiols 82 , but now also to imidazoles 83 or phenols 84 ) on the side chains of amino acids or in conveniently placed spacers. However, in some cases, this synthetic approach can alter the native conformation of the peptide or its biological properties (such as functional activity, binding affinity and/or subcellular localization) 85 .…”
Section: [H1] Bioactive Fluorescent Peptides [H2] Studying Biomoleculmentioning
confidence: 99%
“…In this perspective, 4‐hydroxynon‐2‐enal (HNE) reagent and thiophosphorodichloridate exhibits high chemoselectivity for histidine . Recently, we demonstrated that 2‐cyclohexenone enables the single‐site labeling of His residue and allows late stage installation of probes (Scheme d) . The electrophiles in the previous two examples have been able to overcome the competition with lysine.…”
Section: Single‐site Labeling Of Native Proteinsmentioning
confidence: 99%